Pengaruh Penggunaan Aplikasi Duolingo dalam Meningkatkan Keterampilan Berbicara Bahasa Inggris Siswa Kelas VIII SMPN 43 Padang - syerly indry; Ulfia Rahmi; Zelhendri Zen; Novrianti (STKIP Subang, 2025)
This study aims to determine the effect of using the Duolingo application on improving students' English speaking skills. The research method used was a quasi-experiment with a nonequivalent control group design. This design is similar to a pretest-posttest control group design. Data collection was conducted by testing students' English speaking skills using an English speaking skills assessment rubric and purposive sampling technique was used in sampling with a sample size of 64 students in grade VIII of SMPN 43 Padang in the 2025/2026 academic year, namely 32 students in grade VIII 2 as the experimental class and 32 students in grade VIII 3 as the control class. The research results obtained based on the “Test Statistics” output show that Asymp.Sig (2-tailed) has a value of 0.000. The basis for decision making in the Wilcoxon test is that if the Asymp.Sig value is < 0.05, the hypothesis is accepted, and if the Asymp.Sig value is > 0.05, the hypothesis is rejected. The analysis results show that there is an effect of using the Duolingo application in improving students' English speaking skills and that this media is effective for use in learning. The results of the English speaking ability test for eighth-grade students in the English subject, which was applied to class VIII 2 as the experimental class, obtained a higher average score of 20.69, while the average score obtained in class VIII 3 as the control class was lower with an average of 13.94. Based on the results of this study, the Duolingo application can be recommended as an effective learning medium to improve students' English speaking skills.